Age, personal and family history are independently associated with venous thromboembolism following acute Achilles tendon rupture. Issue 2 (February 2022) - Oliver, William M.; Mackenzie, Samuel A.; Lenart, Lucia; McCann, Conor J.; Mackenzie, Samuel P.; Duckworth, Andrew D.; Clement, Nicholas D.; White, Timothy O.; Maempel, Julian F.
Highlights: The incidence of symptomatic venous thromboembolism (VTE) within 90 days of Achilles tendon rupture (ATR) was low: VTE 3.6%, deep vein thrombosis 2.1%, pulmonary embolism 1.9%. Age ≥50 years, a personal history of VTE/thrombophilia and a family history of VTE were non-modifiable risk factors for VTE following ATR. Non weight-bearing for ≥2 weeks post-injury was a modifiable risk factor for VTE following ATR in our analysis. Abstract: Purpose: The primary aim was to determine independent patient, injury and management-related factors associated with symptomatic venous thromboembolism (VTE) following acute Achilles tendon rupture (ATR). The secondary aim was to suggest a clinical VTE risk assessment tool for patients with acute ATR. Methods: From 2010–2018, 984 consecutive adults (median age 47yrs, 73% [ n = 714/984] male) sustaining an acute ATR were retrospectively identified. Ninety-five percent ( n = 939/984) were managed non-operatively in a below-knee cast (52%, n = 507/984) or walking boot (44%, n = 432/984), with 5% ( n = 45/984) undergoing primary operative repair (<6wks post-injury). VTE was diagnosed using local medical records and national imaging archives, reviewed at a mean 5yrs (range 1–10) post-injury. Multivariate logistic regression was performed to determine independent factors associated with VTE. Results: The incidence of VTE within 90 days of ATR was 3.6% ( n = 35/984; deep vein thrombosis 2.1% [ n = 21/984], pulmonary embolism 1.9% [ n = 19/984]), and the median time to VTE was 24 days (interquartile range 15–44). Age ≥50yrs (adjusted OR [aOR] 2.3, p = 0.027), personal history of VTE/thrombophilia (aOR 6.1, p = 0.009) and family history of VTE (aOR 20.9, p <0.001) were independently associated with VTE following ATR. These non-modifiable risk factors were incorporated into a VTE risk assessment tool. Only 23% of patients developing VTE ( n = 8/35) had a relevant personal or family history, but incorporating age ≥50yrs into the VTE risk assessment tool (alongside personal and family history) identified 69% of patients with VTE ( n = 24/35). Non weight-bearing for ≥2wks after ATR was also independently associated with VTE (aOR 3.2, p = 0.026). Conclusions: Age ≥50 years, personal history of VTE/thrombophilia and a positive family history were independently associated with VTE following ATR. Incorporating age into our suggested VTE risk assessment tool enhanced its sensitivity in identifying at-risk patients. Early weight-bearing in an appropriate orthosis may be beneficial to all patients in VTE risk reduction.